Challenges to Alzheimer Care in Pakistan - Ruzny, Fathima Aamina; Mohamed Imtiyas, Muhammed Ifham; Rizvie, Abdul Raheem (Journal of the Pakistan Medical Association, 2024)
Madam, Alzheimer’s, the prime culprit behind Dementia, is a neurodegenerative disorder that gradually erases memory and cognition, affecting daily tasks 1. Symptoms often emerge in later years, and in Pakistan, where a rising aging population and middle-income status prevail, the risk amplifies. By 2030, global dementia cases can soar to 1.3 million from 850,000 in 2015, surging to 3.6 million by 2050 without preventive action 2. Urgent attention beckons. Yet, challenges abound. With Pakistan’s depleting literacy rate currently of 58.9% in 2023, misconceptions are likely 3. Stigma, cultural norms, and language barriers shroud the path to treatment. Moreover, mental health issues like depression, an Alzheimer’s symptom, are seen as taboo, deterring help-seeking. Till date, the lack of national databases stifles research progress, and a shortage of neurologists-just less than 150 for millions of people-worsens with scarce training programs4. Private caretakers in this developing country may be limited. As this chronic Alzheimer’s has no cure, high drug costs hinder adherence, while the affordability of the new "Leqembi" drug, if approved, raises concerns. Additionally, access to MRI and CT scanning equipment in Pakistan is not widespread and their procurement along with testing entail significant costs. Furthermore, government policies and funding for Alzheimer’s treatment and research might be insufficient with the rising aging population. NGOs in Pakistan related to Alzheimers are very limited- “Alzheimers Pakistan” the one and only centered in just three regions across this vast country. Solutions for these challenges emerge as vibrant threads. How can we aid patients and families in Alzheimer education? Imagine engaging workshops and media partnerships with prominent figures like the UNICEF Goodwill ambassadors thereby igniting a good community-healthcare bond, and envision ‘Alzheimer homes’ for patients lacking caregivers. Besides, a national database involving stakeholders, from NGOs to healthcare providers, can not only pave the way for easy data accessibility but also to proper treatment plans and protocols. Engaging these stakeholders could also lead to initiatives for more affordable medicines. For the shortage of neurologists, medical tourism initiatives that attract foreign neurologists to work temporarily in the country, sharing their expertise and contributing to healthcare delivery can be deployed. Targeted training for healthcare professionals and collaborating with international organizations for increased research, clinical trial participation and even in machinery purchase hold a promise to resolving this issue. Conclusively, emphasizing these concerns holds utmost significance in the pursuit of discovering effective interventions for this incurable ailment.